"It's celebrating our humanity" - A Single Case Study Investigation of the Education Human Values Model and its Relationship to Pupil Wellbeing and Flourishing in a Dublin Primary School - Caffrey, Christina (Marino Institute of Education, 2022)
The NCCA Draft Primary Curriculum Framework proposes a designated curriculum area for Wellbeing in the upcoming revisions to the Irish Primary Curriculum. To address this provision, the inclusion of a subject entitled Social, Personal, and Values Education is under consideration (NCCA, 2020). Values education encompasses, “a national movement creating schools that foster ethical, responsible, and caring young people, by modelling and teaching good character through emphasis on universal values that we all share” (Berkowitz & Bier, 2005, p.2). This study examines the efficacy of Education in Human Values (EHV), a values education model originating from the teachings of the Indian spiritual leader, Sri Sathya Sai Baba. Underscored by the philosophy of Educare, the EHV approach is proposed to draw out the inherently latent human values of love, truth, peace, right conduct, and non-violence (SSIO, 2018). This study examines the potential of the EHV model to effectively deliver the Wellbeing Curriculum area of the revised Irish Primary Curriculum. A social constructivist paradigm was adopted for this study in order to examine the lived reality of pupils and educators with respect to the implementation of EHV in a Dublin primary school. A single case study investigation, incorporating one-to-one semi-structured interviews with three educators, and a single focus group interview with five 6th class pupils was completed. Data analysis yielded a perceived positive correlation between EHV and the enhancement of pupil social and emotional learning and associated psychological wellbeing, across both educator and pupil interviews. Other pertinent findings concerning the universal applicability of this model with respect to whole-school implementation, cross curricular integration, and ethos, were also revealed. These findings coupled with the model’s alignment with a flourishing paradigm of success, highlight EHV as a serious contender for leading wellbeing promotion in the new curriculum.
Keywords: Curriculum planning; Wellbeing; Irish Primary Curriculum; Education, Primary; Social values; Qualitative research; Semi-structured interviews; Whole-school implementation; Cross curricular integration; Ethos; Curriculum planning; Wellbeing; Education, Primary; Social values; Qualitative research; Semi-structured interviews